ANALISIS GARAP LANCARAN GAGAK SETRA DALAM PAKELIRAN GAYA YOGYAKARTA - Amrih Tuti Lestari; Bayu Wijayanto; R. Bambang Sri Atmojo (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2021)
The research entitled Lancaran Gagak Setra in Pakeliran Gaya Yogyakarta discusses pathet, garap, presentation structure, performance structure, and the transition of pathet Lancaran Gagak Setra in the budhalan scene in pakeliran style in Yogyakarta. This study uses a qualitative research approach with descriptive analysis research methods by analyzing in two contexts, namely textual and contextual. The textual analysis in this study analyzes the pathet, the transition of Lancaran Gagak Setra in the Yogyakarta style pakeliran, the musical factors considered in the pathet transition, and the structure of the Lancaran Gagak Setra presentation in the Suryatmaja Krama theater play by analyzing the work of several ricikan. Contextual analysis analyzes the structure of the Lancaran Gagak Setra performance in the budhalan scene in the Suryatmaja Krama play. Gagak Setra is one of the genres used in the budhalan scene with calluses or jaranan in the Yogyakarta style pakeliran. Lancaran Gagak Setra in the Yogyakarta style pakeliran is presented in the realm of pathet nem time, however, the balungan gending Lancaran Gagak Setra focuses more on pathet sanga. The difference in pathet in the realm of presentation time results in differences in the perception of pathet in Lancaran Gagak Setra. The presentation of the Lancaran Gagak Setra in different packages, of course, has a pathet transition. There are musical factors to consider in this pathet transition. Bendhe Tengara is the transition from pathet manyura to pathet sanga, and grambyangan is the transition from pathet sanga to pathet nem. These two musical factors will make the transition between pathet nem, manyura, sanga, and nem happen slowly or gradually. A sense of pathet is achieved from Lancaran Gagak Setra, which supports the dramatic atmosphere in the budhalan scene with calluses in the Yogyakarta-style pakeliran.